Recent development of integrating CO2 hydrogenation into methanol with ocean thermal energy conversion (OTEC) as potential source of green energy. Issue 1 (2nd January 2023) - Zulqarnain,; Mohd Yusoff, Mohd Hizami; Keong, Lau Kok; Yasin, Nor Hafizah; Rafeen, Mohammad Syamzari; Hassan, Amiruddin; Srinivasan, Geetha; Yusup, Suzana; Shariff, Azmi Mohd; Jaafar, A. Bakar
ABSTRACT: Renewable energies have gained momentum in energy transition agenda based on the benefit of lower emissions of carbon and its compounds. Many technologies have been developed at different technology readiness levels addressing climate change impact with reduced emissions of greenhouse gases such as CO2 . Herein the perspective article, we have reviewed CO2 capture technologies, such as absorption, adsorption, membrane separation, cryogenic separation and separation via hydrate formation, with further focus on the possibility of utilising ocean thermal energy conversion (OTEC) power to generate green hydrogen and produce low carbon fuels. The potential of OTEC generated hydrogen to produce methanol was explored using a simulation exercise utilising a scenario from a real-life offshore gas production facility. By varying the catalysts and reaction conditions, the findings showed encouraging results of CO2 conversion of ≥50% and product yield of ≥80%. Considering single path reaction with 90%, 95% and 99% of recycling, the highest prediction of methanol production coupled with CO2 hydrogenation process was 276.59 metric tonnes per day (MTPD). In addition, based on the assumption of 13.5 million standard cubic feet per day (MMSCFD) of CO2 produced, 204 MW of OTEC power is required to convert approximately 97.82 MTPD of hydrogen for methanol production making it potentially an industrially viable process. GRAPHICAL ABSTRACT: UF0001